2 MINAT SISWA SMP MEMILIH JURUSAN JASA BOGA PADA SMK DI KOTA MADYA PADANG - Prasetyo, Ikhsan; Faridah, Anni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aimed to describe (1) the interests of junior high school students choosing majors based Hospitality at SMK intrinsic factor (2) interest in junior high school students choose majors Hospitality at SMK by extrinsic factors. This research uses descriptive method. The study population was selurus class X students majoring in Hospitality at SMK Padang municipality totaling 325 students. The sample was simple random sampling (simple random sample) is class X majoring in Hospitality at SMK Padang Municipality of as many as 150 students. Data collection techniques in this study using a questionnaire. Data were analyzed using propensity test and percentage calculations. The results showed that the trend analysis of junior high school students to choose a major in Hospitality at SMK Padang municipality of internal factors are the willingness factor 44% in the high category. Factors feeling happy 40% in medium category. 70.66667% motivational factors included in the medium category. While external factors that support families with percentage 45.33333% included in the medium category. 53.33333% of the school environment factors included in the medium category. Community environmental factors 56% in medium category. Factors mass media 53.33333% medium category.Kata kunci: Interest, Student, Department of Hospitality, SMK.